Structure of Models for Aggregate Assessment of Financial Risk Commercial Banks - Кришталь, Г. (Київський національний університет імені Тараса Шевченка, 2016)
Розглянуто концептуальні підходи застосування структурної моделі для оцінки фінансового ризику комерційних банків, а саме, вимірювання ризиків в комплексі: порівняння розміру капіталу, розрахованого на основі стандартного підходу Базеля ІІ, просунутого підходу Базеля ІІ і структурної моделі. Аналіз результатів застосування моделі в ситуації економічної кризи, а саме достатності капіталу комерційних банків. Висвітлено єдиний підхід до вибору міри ризику і його параметрів, для вимірювання ризиків різної природи.

Conceptual approaches use a structural model for assessment of financial risk commercial banks, namely the risk measurement in combination: a comparison of its capital, calculated based on the standard approach of Basel II advanced approaches of Basel II and the structural model. Analysis of the application of the model in a economics crisis situation, such as the capital adequacy of the commercial banks. Deals with a unified approach to the choice of measure and its risk parameters to measure the risks of different nature. There was also a speaker examined risk factors and the corresponding volumes of portfolios at risk, per month from 2014 to 2015 for the commercial banks, namely the weighted average yield on loans (including the reserve) individuals, legal entities, banks; the average cost of deposits of individuals and legal entities; market portfolio yield securities (RTS Index); the share of administrative and economic costs in the assets of the bank. For each risk factor were built parametric approximation of their historical distributions. Graphically shows the distribution, yield corporate loan portfolio, the cost of redundancy, the cost of deposits of individuals and entities that reflect the behavior of risk factors in conditions of economics crisis.
Застосування структурної моделі для оцінки сукупного фінансового ризику комерційних банків
Keywords: фінансові ризики; комерційні банки; активи; Базель; структурна модель; Conceptual approaches use a structural model for assessment of financial risk commercial banks; namely the risk measurement in combination: a comparison of its capital; calculated based on the standard approach of Basel II advanced approaches of Basel II and the structural model. Analysis of the application of the model in a economics crisis situation; such as the capital adequacy of the commercial banks. Deals with a unified approach to the choice of measure and its risk parameters to measure the risks of different nature. There was also a speaker examined risk factors and the corresponding volumes of portfolios at risk; per month from 2014 to 2015 for the commercial banks; namely the weighted average yield on loans (including the reserve) individuals; legal entities; banks; the average cost of deposits of individuals and legal entities; market portfolio yield securities (RTS Index); the share of administrative and economic costs in the assets of the bank. For each risk factor were built parametric approximation of their historical distributions. Graphically shows the distribution; yield corporate loan portfolio; the cost of redundancy; the cost of deposits of individuals and entities that reflect the behavior of risk factors in conditions of economics crisis.